Do lugar do lingüista e da língua como objeto de divulgação - Cervo, Larissa Montagner (2008)
The aim on this research is to promote a reflection concerning language signifying as a divulgation object within capitalist society where all becomes a consumption product. In this scene, language is a subject in the scientific divulgation discourse however it is a marginal historical position and linked to utilitarian senses and based on the empirical perspective of science. In order to analyze this conjuncture, we adopted the theoretical basis of Discourse Analysis, by Michel Pêcheux, and Eni Orlandi and fellows, in Brazil. The corpus is constituted by two magazines A Cigarra Magazine (1950s) and Língua Portuguesa (2000s) which represent different stages in the discursive process and emphasize language as a divulgation object. From these publications, we focus texts written by linguists, Joaquin Mattoso Câmara Jr. and José Luiz Fiorin with the purpose of analyzing the way in which they mean themselves on the position of divulgators, observing the constitutive vestiges of the discourse. Our study shows that language signifying as a product in the scientific discourse divulgation and its diffusion is the manifestation of a pretext. Furthermore the presence of linguists on these Medias underlines need of divulging language sciences toward recognition and attention of public politics and society in general.